Peran Pemerintah Dalam Meningkatkan Transaksi Dan Kerjasama Ekonomi - Rani Winata (Business and Enterpreneurship Journal (BEJ), 2023)
In connection with the development of the times, Indonesia is currently conducting international transactions and cooperation that aims to be able to prosper the community. This research was conducted with the aim of knowing the government's role in international economic transactions and cooperation. The research was carried out in the form of descriptive qualitative by collecting data using literature and summarizing the results of theories or opinions that had been done previously. The results show that Indonesia has made progress in the economic sector which has made the country prosperous. In connection with the existence of bilateral transactions and cooperation, the government plays an active role in this cooperation, where the exports and imports that can be carried out by the government to establish this cooperation make all parties mutually beneficial. The government uses fiscal policy by imposing tariffs on every exported or imported goods. Keywords: role of government, transactions, international cooperation